Novelties and notes in Lindsaea (Lindsaeaceae) from Mexico and central America - Rojas Alvarado, Alexander (2017)
Three new species of Lindsaea are described and illustrated from Mesoamerica: L. angustipinna, L. fuscopetiolata and L. mesoamericana. Additionally, the status of L. quadrangularis subsp. subalata is modified to L. subalata and Lindsaea horizontalis and L. moritziana Klotzsch are reinstated as valid species. New records of L. cubensis, L. divaricata L. horizontalis and L. leprieurii are reported from several countries in the area. A key to the species of Lindsaea in Mexico and Central America is provided.